The Concept of Divine Decree in the Prophet’s Hadiths: A Theological Study of Faith, Human Effort, and God’s Determination - Maulana Maulana; Moh Masduki; Dawam Multazamy Rohmatulloh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study explores the concept of qadar (Predestination) in the Prophet Muhammad’s hadiths, focusing on the theological relationship between faith, human effort, and God’s determination. Using a qualitative-descriptive approach through library research, this paper examines canonical hadith collections such as Sahih al-Bukhari, Sahih Muslim, Sunan al-Tirmidhi, and Musnad Ahmad ibn Hanbal. Employing a maudhū‘i (thematic) method, the study identifies and analyzes hadiths that articulate the dynamic balance between divine will and human agency. The findings reveal that the Prophet’s hadiths on destiny do not deny human freedom to act but instead integrate human effort as an intrinsic part of God’s decree. From a classical theological perspective, the Asy‘ari and Maturidi concepts of kasb and ikhtiyar highlight the harmony between divine omnipotence and human moral responsibility. Meanwhile, modern contextual theology—as represented by Fazlur Rahman, M. Quraish Shihab, and Khaled Abou El-Fadl—reinterprets the hadiths ethically, positioning faith in divine decree as a source of spiritual resilience and proactive engagement with life. Consequently, the study concludes that the Prophet’s teaching on qadar represents a theology of balance—affirming that true faith inspires active spirituality and moral responsibility amid the complexities of modern existence